UJI VALIDITAS MULTIMEDIA INTERAKTIF ETNOMATEMATIKA BANGUN RUANG BERBASIS CANVA TERINTEGRASI 3D PADA KELAS VI SD - L, Assalwa Tazkiya; Sastrawati , Eka; Putri, Andi Gusmaulia Eka (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Technology development has shaped students’ learning habits that are increasingly aligned with digital devices; however, geometry instruction in Grade VI at SDN 220/III Pugu still relies heavily on two-dimensional resources and limited solid-geometry manipulatives. This condition may hinder the achievement of the Phase C geometry learning outcomes in the Merdeka Curriculum, particularly the ability to construct and decompose cubes and rectangular prisms (including composite solids) and to determine front, top, and side views. This study aimed to develop and validate a three-dimensional integrated interactive learning multimedia product grounded in the ethnomathematics context of the Masjid Agung Kerinci for Grade VI solid geometry. A research and development approach was employed using the ADDIE model, limited to the development stage, comprising curriculum and needs analysis, analysis of student characteristics and facilities, design using storyboards and flowcharts, functional testing, and expert validation. The product was developed in Canva and utilized the Canva AI-Code feature to embed interactive elements and three-dimensional visualizations in a 1920 × 1080 link-based presentation containing information menus, user guidelines, learning materials, exercises, reflection activities, and inter-slide navigation. Validation involved three experts in content, language, and media using a 1–5 Likert scale, with qualitative feedback and quantitative analysis through validity percentages. The results indicated very high validity across all aspects: content validity 94%, language validity 96%, and media validity 93.33%, followed by revisions focusing on strengthening introductory content, refining language accuracy, and clarifying device recommendations. In conclusion, the developed three-dimensional interactive multimedia is feasible as a supporting medium for Grade VI solid-geometry learning and can be advanced to the implementation stage to examine practicality and its impact on learning outcomes. ABSTRAKPerkembangan teknologi membentuk pola belajar peserta didik yang semakin dekat dengan perangkat digital, tetapi pembelajaran geometri di kelas VI SDN 220/III Pugu masih dominan mengandalkan sumber dua dimensi dan alat peraga bangun ruang yang terbatas. Kondisi tersebut berpotensi menghambat pencapaian elemen geometri Fase C Kurikulum Merdeka, terutama pada kompetensi mengonstruksi dan mengurai kubus serta balok beserta gabungannya dan menentukan tampak depan, atas, dan samping. Penelitian ini berfokus pada pengembangan serta uji validitas multimedia pembelajaran interaktif terintegrasi tiga dimensi berbasis etnomatematika Masjid Agung Kerinci pada materi bangun ruang kelas VI. Metode yang digunakan adalah penelitian dan pengembangan dengan model ADDIE yang dibatasi sampai tahap pengembangan, meliputi análisis kurikulum, kebutuhan, karakteristik peserta didik, dan sarana prasarana; perancangan melalui storyboard dan flowchart; pengembangan produk disertai uji fungsional; serta validasi ahli. Produk dikembangkan menggunakan Canva dan memanfaatkan fitur Canva AI-Code untuk menyematkan elemen interaktif dan visualisasi tiga dimensi dalam format presentasi 1920 × 1080 berbasis tautan, yang memuat menu informasi, petunjuk penggunaan, materi, latihan, refleksi, dan navigasi antarslide. Validasi melibatkan ahli materi, bahasa, dan media menggunakan skala Likert 1–5 serta dianalisis secara kualitatif dan kuantitatif melalui persentase. Hasil menunjukkan tingkat validitas sangat tinggi pada aspek materi sebesar 94%, bahasa 96%, dan media 93,33%, dengan perbaikan pada penguatan pengantar materi, penyuntingan kebahasaan, dan penegasan rekomendasi perangkat. Dengan demikian, multimedia yang dikembangkan dinyatakan layak sebagai media pendukung pembelajaran bangun ruang kelas VI dan dapat dilanjutkan pada tahap implementasi untuk menguji kepraktisan serta dampaknya terhadap capaian belajar.